Rethinking the Complexities of the Body and Disability: Theological Account - Vuk Grgic, Martina (Religions, 2024)
The biological aspect of human embodiment frequently constitutes the primary basis for personal assessment, with an emphasis on rationality, free choice, material well-being, and happiness as fundamental attributes of worth. This perspective is also evident in cultural practices of body modification, which reflect societal standards and identity expression. The promotion of standards of bodily appearance that are often considered unrealistic within contemporary culture has the effect of creating a social environment in which those who do not conform to these standards are rejected and stigmatized. This can include individuals with disabilities, the elderly, or those with chronic illnesses and different bodily appearances. In the majority of cases, the so-called ‘body capital’ culture views the disabled body through the lens of a person’s physical appearance, which is, to a certain extent, associated with a biological dysfunction or reflects a kind of physical disability or vulnerable corporeality. This paper seeks to examine perspectives on the body through the lenses of major discourses surrounding disability, biblical anthropology, and disability theology. These perspectives advocate for the intrinsic dignity and value of the disabled body, challenging contemporary norms and projections upon the body, by underscoring the biographical, interdependent, and spiritual dimensions of human embodiment. This approach stands as an alternative to the reductionist view of the body, which prioritizes physical attributes over a comprehensive understanding of complete personhood.